DESCRIBING COMPUTATIONAL DOMAINS IN APPLICATIONS FOR SOLVING THREE-DIMENSIONAL PROBLEMS OF TECHNOLOGICAL PROCESSES - Turakulov, Azambek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article discusses the problems encountered in the creation of computer programs for solving three-dimensional problems of mathematical physics. The complexity of describing areas of problem solving for a computer is explained. A method of representing three-dimensional areas in the form of combinations of geometric shapes is proposed. A method for obtaining images of a flat section of the three-dimensional regions using the construction of a grid is discussed. A method for determining the location of points relative to three-dimensional areas is proposed.